Iso Series Certification System on The Financial Performance and Performance - Tri Widyastuti (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
The objective of this study was to compare the financial performance and stock performance of companies with and without ISO series certifications. In this study, EVA (Economic Value Added) and financial ratios, particularly Debt to Equity, Return on Equity, and Return on Assets, reflect financial performance, while anomalous returns represent stock performance. This study utilizes data from 2011 to 2019 firm reports that have acquired ISO 9000 and 14000 series certification. The results indicate that organizations with ISO series certification and those without certification are comparable. There is no substantial difference between the EVA and ROE ratios' financial performance. Nevertheless, the DER and ROA financial performance ratios differ significantly. Moreover, there are considerable discrepancies between ISO corporations and non-ISO companies in terms of stock performance. The conclusion of the study is that there is no significant difference between the performance of companies that receive ISO certification and those that do not, as a result of insufficient research time, the fact that non-ISO companies already have good marketing management, and the lack of continued ISO implementation in companies that already have ISO certification.